P216 Oral Budesonide and low serum albumin levels at surgery are associated with a higher risk of postoperative intra-abdominal septic complications after primary ileocecal resection for Crohn's disease: a retrospective analysis of 853 consecutive patients treated in a tertiary centre. (30th January 2023) - Dajti, G; Cardelli, S; Rizzello, F; Gionchetti, P; Poggioli, G; Rottoli, M
Abstract: Background: Patients undergoing ileocecal resection for Crohn's disease (CD) are at high risk of postoperative intra-abdominal septic complications (IASC). The associated risk factors are still debated. The aim of the study was to identify the variables associated with IASC in patients treated for primary CD of the terminal ileum. Methods: Retrospective single-centre study including consecutive patients undergoing ileocecal resection for CD between 2004-2021 and managed before surgery in a multidisciplinary IBD unit. Outcomes: to identify the variables associated with IASC (primary aim) and severe complications, classified as Clavien-Dindo grade 3 and higher (secondary aim). The potential independent predictors of each outcome were evaluated using logistic regression. To reduce overfitting, all models were built including only the variables that were significant at univariate analyses, except for age, gender and history of cardiovascular diseases, that were included a priori. Standard diagnostic procedures were adopted to check all models validity: influential observation analysis (Dbeta, change in Pearson chi-square), Hosmer-Lemeshow test for the goodness of fit and C statistic (area under the Receiving Operator Curve). Results: A total of 853 patients were included. Overall sample characteristics are shown in Table 1. Table 2 and Table 3 reported the comparison according to the primary (IASC) and secondary (severe complications) outcomes, respectively. Table 4 showed the multivariate analyses of the potential predictors of IASC and severe complications. The onset of IASC was associated with lower serum albumin level (OR 1.81, 95% CI 1.15-2.94, p=0.011) and the use of oral budesonide at time of surgery (OR 2.07, 95% CI 1.12-3.83, p= 0.021). The risk of severe complications was associated with a history of cardiovascular disease (OR 2.91, 95% CI 1.08-7.84, p=0.03) and lower serum albumin level (OR 1.58, 95% CI 1.02-2.50, p=0.04). Conclusion: The present study analysed a large population of patients affected by CD of the terminal ileum who were treated homogeneously before surgery in a multidisciplinary setting and confirmed the significant impact of preoperative nutritional status on the risk of severe postoperative complications and IASC. The latter, however, was also associated with the use of oral budesonide at the time of surgery. This finding has not been previously reported in the literature. Based on the present evidence, oral budesonide should be discontinued or tapered to the lowest dose before surgery.